Research and Practice of the Support Service System for the Professional Development of Rural Middle School English Teachers: A Case Study of Hengyang City, Hunan Province - He, Xueyun; Mo, Linhui; Liu, Jin; Wang, Chao; Xu, Jie (Pacific International Journal, 2025)
This study investigates the support service system for the professional development of rural middle school English teachers, using Hengyang City, Hunan Province, as a case study. Through surveys on the current status of rural English teachers’ professional development in Hengyang, critical challenges were identified, including insufficient teaching staff, weak disciplinary knowledge, limited training opportunities, low participation in teaching research activities, and reduced job satisfaction. To address these issues, a four-module support service system was developed, integrating expert lectures, micro-lecture collections, project applications, and collaborative teaching research activities. By leveraging resources from universities, government agencies, educational research institutes, and schools, this system significantly enhanced teacher engagement in professional development, enriched teaching resources, improved pedagogical competencies, and elevated student academic performance.